Investment in Fixed Assets and Firm Profitability: Empirical Evidence from the Nigerian Banking Sector - E, Olatunji, Toyin; A, Adegbite, Tajudeen (Asian Journal of Social Sciences and Management Studies, 2014)
The study examined the effect of investment in fixed assets on profitability of selected Nigerian banks. It also analyzed the significant components of fixed assets investment of selected Nigerian Commercial Banks. Data were obtained from annual reports and accounts of selected Nigerian commercial Banks. Pearson product moment correlation and multiple regressions were employed to analyze the relationship between the dependent variable (Net profit) and independent variables (Building, Land, Leasehold premises, fixtures and fitting, and investment in computers.). Findings show that there is a significant relationship between dependent variable (Net Profit) and the independent variables (Building, information communication and technology, machinery, leasehold, land and fixture and fitting) with the adjusted R2 @ 96%. Therefore, investments in fixed assets have strong and positive statistical impact on the profitability of banking sector in Nigeria. In order to improve bank profitability through efficient management of fixed assets, Nigerian banks should increase fixed assets investments in form of ICT. Fixed assets utilization and productivity needs to be monitored to boost profitability for shareholders’ satisfaction.